Older adult stroke survivors’ needs and perspectives of a stroke app: a qualitative study - Wenjing Cao; Afang Li; Azidah Abdul Kadir; Juan Chen; Lanying Chen; Qing Li; Intan Idiana Hassan (BMC Geriatrics)
Abstract Background Stroke continues to be the second leading cause of death and a significant contributor to disability globally, with a more pronounced impact on older adults compared to other age groups. Along with evidence that mobile health (mHealth) apps have promising possibilities for supporting individuals pursuing health and wellness goals, the development of stroke apps is increasing. However, there remains a notable lack of research investigating the needs and perspectives of stroke survivors during the development of such apps. Objective We aimed to describe the needs and perspectives of older adult stroke survivors regarding a stroke app. Methods We employed an empirical phenomenological approach for a qualitative study. Using purposive and snowball sampling, older adult stroke survivors were recruited from three tertiary hospitals in Hunan province. Face-to-face semi-structured interviews were conducted between August and October 2024. Data were transcribed verbatim and analysed using Haase's adaptation of Colaizzi's phenomenological method. Findings Thirteen older adult stroke survivors (eight men and five women aged 63–84 years) participated in the study in China. Three main categories and ten subcategories were extracted. The themes were the following: (1) optimism about the app (a good thing and eager to use); (2) desire for an app tailored to the unique (particular to older adults, information at fingertips, and reminding); and (3) concern (privacy issues, more depersonalized interactions with their doctors, the validity of the information provided on the app, cost, and having problems in using the app). Conclusion This study pinpointed crucial factors from users' needs and perspectives that should be considered in developing a mobile app for older adult stroke survivors. Future research on app development should gather users' needs and preferences to enhance acceptability and increase the likelihood of successful implementation.